Um desenho de luz: o princípio físico da câmera fotográfica - GONÇALVES, Nadiane Pantoja (2024)
In this work we study one of the main fundamental concepts of science, which is light, using a very popular instrument in our society, called CAMERA PHOTOGRAPHIC. The objective of this work is to present a brief summary of the historical context of its development, as it has been improved, relations with the physical phenomena of optics and quantum physics, light being one of the main concepts that permeate our modern scientific knowledge, as well as the tecnologies used. Thus, we can call it the “Cervical spine” of Science. This concept is used at various levels of education, fron basic to higher education. At the same time, we understand that photography emerges as an important context for teaching the concept of light and its properties. In this way, this work presents a conceptual discussion about the light and its properties, besides bringing some episodes of the history of the Science on the development of this field of the physins. So we can see that it goes far beyond wath we imagined, and that it is our guidebook for understanding the funtioning of the universe inside and outside our planet.